Picture free recall performance linked to the brain's structural connectome. Issue 7 (23rd May 2017) - Coynel, David; Gschwind, Leo; Fastenrath, Matthias; Freytag, Virginie; Milnik, Annette; Spalek, Klara; Papassotiropoulos, Andreas; de Quervain, Dominique J.‐F.
Abstract: Introduction: Memory functions are highly variable between healthy humans. The neural correlates of this variability remain largely unknown. Methods: Here, we investigated how differences in free recall performance are associated with DTI‐based properties of the brain's structural connectome and with grey matter volumes in 664 healthy young individuals tested in the same MR scanner. Results: Global structural connectivity, but not overall or regional grey matter volumes, positively correlated with recall performance. Moreover, a set of 22 inter‐regional connections, including some with no previously reported relation to human memory, such as the connection between the temporal pole and the nucleus accumbens, explained 7.8% of phenotypic variance. Conclusions: In conclusion, this large‐scale study indicates that individual memory performance is associated with the level of structural brain connectivity. Abstract : Although memory capacities vary between individuals, the neural correlates of such variability remain largely unknown. In a large study of 664 healthy young individuals, we investigated if white matter connections throughout the human brain are related to individual recall performance. Our results demonstrate that a set of connections, mainly between the occipital and temporal lobes, explained 7.8% of variability in memory performance.